Reproductive Health Training in 2026 and Beyond: Adapting Abortion Education in a Post-Dobbs Era - Ameek Kaur Bindra; Sarah C. Mozden; Kasey Nguyen; Meenakshi Singhal; Tuyet-Mai Ha Hoang (Journal of Medical Education and Curricular Development, 2026)
The 2022 Supreme Court decision in Dobbs v. Jackson Women’s Health Organization devolved abortion regulation to individual states, producing a fragmented legal environment that complicates clinical education in obstetrics and gynecology (Ob/Gyn). In this Scholarly Perspective, we develop four sequential arguments. First, post-Dobbs legal fragmentation has materially constrained the infrastructure of abortion training, including the geographic distribution of Complex Family Planning (CFP) fellowships and the reliance on interstate rotations. Second, comprehensive reproductive health training matters not only for elective abortion provision but also for the procedural and counseling skills required to manage miscarriage, ectopic pregnancy, and obstetric emergencies – clinical needs that exist in every state. Third, even where abortion remains legal, the Accreditation Council for Graduate Medical Education’s (ACGME) opt-out training requirement has not been uniformly implemented, and 46% of U.S. Ob/Gyn residency programs lack routine abortion training across all states. Fourth, a coordinated response is feasible and should focus on protected interstate training partnerships, sustained support for CFP fellowships, expansion of validated online and simulation-based curricula, and clearer enforcement of national training standards. We close by acknowledging the limits of training reform: educational adaptation can mitigate, but cannot substitute for, the policy changes required to restore equitable access to reproductive health care.